2018
DOI: 10.1103/physrevaccelbeams.21.064201
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical bunching and density peaks in expanding Coulomb clouds

Abstract: Expansion dynamics of single-species, non-neutral clouds, such as electron bunches used in ultrafast electron microscopy, show novel behavior due to high acceleration of particles in the cloud interior. This often leads to electron bunching and dynamical formation of a density shock in the outer regions of the bunch. We develop analytic fluid models to capture these effects, and the analytic predictions are validated by PIC and N-particle simulations. In the space-charge dominated regime, two and three dimensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 74 publications
1
38
0
Order By: Relevance
“…Specifically, we showed that a density shock, seen in Coulomb explosion studies [5-8, 20, 27, 34], was present in the analytic density evolution of initially Gaussian distributions under both cylindrical and spherical symmetries but absent under planar symmetry unless an appropriate initial chirp in phase space is present. Moreover, such a shock is absent in nonrelativistic dynamics of uniform systems with cold initial conditions suggesting that uniform distribution evolution is unique in this regard [19]. We noted in our previous work that the density evolution seen in PIC simulations using an electromagnetic (EM) solver and relativistic particle pusher, which should capture all relativistic effects if the initial field is accurate, do not significantly differ from our analytic description for the densities analyzed there [19].…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…Specifically, we showed that a density shock, seen in Coulomb explosion studies [5-8, 20, 27, 34], was present in the analytic density evolution of initially Gaussian distributions under both cylindrical and spherical symmetries but absent under planar symmetry unless an appropriate initial chirp in phase space is present. Moreover, such a shock is absent in nonrelativistic dynamics of uniform systems with cold initial conditions suggesting that uniform distribution evolution is unique in this regard [19]. We noted in our previous work that the density evolution seen in PIC simulations using an electromagnetic (EM) solver and relativistic particle pusher, which should capture all relativistic effects if the initial field is accurate, do not significantly differ from our analytic description for the densities analyzed there [19].…”
Section: Introductionmentioning
confidence: 62%
“…sets the timescale for the relativistic expansion of high density charge clouds; as was found in the non-relativistic cases [19]. In addition to the plasma frequency, we find it advantageous to define the related 1D-number density as…”
Section: Fundamental Parametersmentioning
confidence: 75%
See 3 more Smart Citations